Correction to: Constructing mathematical bitterness scale related to teacher factor - Dirgantoro, Kurnia Putri Sepdikasari; Soesanto, Robert Harry; Yanti (Jurnal Elemen, 2025)
Correction to: Jurnal Elemen, Vol. 10 No. 2, May 2024, p. 395-409 https:/doi.org/10.29408/jel.v10i2.25508 The original version of this article unfortunately contained a mistake. The article contains a duplication of table numbers, specifically Table 2, resulting in a disruption of the sequential order of tables. Additionally, several citations are absent from the reference list, including Lima et al. (2019); McGee & Spencer (2021); Elliot & Bachman (2018); Durksen et al. (2017); Jais et al. (2019); Mammana & Pennisi (2011); Sierpinska et al. (2008); Heyder et al. (2019); and Carmichael et al. (2017). The original article has been corrected. The original article can be found online at https://doi.org/10.29408/jel.v10i2.25508